Hydrothermal Synthesis of a rGO Nanosheet Enwrapped NiFe Nanoalloy for Superior Electrocatalytic Oxygen Evolution Reactions. Issue 41 (23rd August 2016) - Geng, Jing; Kuai, Long; Kan, Erjie; Sang, Yan; Geng, Baoyou
Abstract: Graphene‐based hybrid nanostructures possess many advantages in the field of electrochemical energy applications. In this work, a facile and efficient hydrothermal approach has been developed for the preparation of NiFe alloy nanoparticles/rGO hybrid nanostructures, in which the nanoparticles are well combined with rGO nanosheets and the size of the nanoparticles is about 100 nm. Moreover, the electrochemical oxygen evolution reaction (OER) tests confirmed that the obtained NiFe/rGO hybrid nanostructures possess notably higher activity than both the rGO‐free NiFe nanoparticles and pure Ni/rGO hybrids, and the optimal NiFe ratio is 2:1. The OER overpotential at 20 mA cm −1−2 with Ni2 Fe/rGO is as low as 0.285 V, which is 96 mV lower than that of pure Ni/rGO hybrids. Meanwhile, the Ni2 Fe/rGO catalyst has excellent stability. Therefore, this work contributes a facile and efficient method to prepare a NiFe alloy nanoparticles/rGO hybrid structure for potential applications in the field of electrochemical energy devices, such as electrochemical water splitting cells, rechargeable metal/air batteries, etc. Abstract : Metallic Ni2 Fe nanoalloy/rGO hybrids : A highly active electrocatalyst for the oxygen evolution reaction. A mild hydrothermal reduction route has given birth to a well‐shaped rGO nanosheet enwrapped NiFe nanoalloy. Moreover, the obtained Ni2 Fe nanoalloy/rGO hybrids present notable activity over the rGO free materials (see figure).